A Transgenic Camelina sativa Seed Oil Effectively Replaces Fish Oil as a Dietary Source of Eicosapentaenoic Acid in Mice. Issue 2 (20th January 2016) - Tejera, Noemi; Vauzour, David; Betancor, Monica B; Sayanova, Olga; Usher, Sarah; Cochard, Marianne; Rigby, Neil; Ruiz-Lopez, Noemi; Menoyo, David; Tocher, Douglas R; Napier, Johnathan A; Minihane, Anne Marie
Abstract: Background: Fish currently supplies only 40% of the eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) required to allow all individuals globally to meet the minimum intake recommendation of 500 mg/d. Therefore, alternative sustainable sources are needed. Objective: The main objective was to investigate the ability of genetically engineered Camelina sativa (20% EPA) oil (CO) to enrich tissue EPA and DHA relative to an EPA-rich fish oil (FO) in mammals. Methods: Six-week-old male C57BL/6J mice were fed for 10 wk either a palm oil–containing control (C) diet or diets supplemented with EPA-CO or FO, with the C, low-EPA CO (COL), high-EPA CO (COH), low-EPA FO (FOL), and high-EPA FO (FOH) diets providing 0, 0.4, 3.4, 0.3, and 2.9 g EPA/kg diet, respectively. Liver, muscle, and brain were collected for fatty acid analysis, and blood glucose and serum lipids were quantified. The expression of selected hepatic genes involved in EPA and DHA biosynthesis and in modulating their cellular impact was determined. Results: The oils were well tolerated, with significantly greater weight gain in the COH and FOH groups relative to the C group ( P < 0.001). Significantly lower (36–38%) blood glucose concentrations were evident in the FOH and COH mice relative to C mice ( P < 0.01). Hepatic EPA concentrations were higher in all EPA groups relative to the C group ( P < 0.001), with concentrations of 0.0, 0.4, 2.9, 0.2, and 3.6 g/100 g liver total lipids in the C, COL, COH, FOL, and FOH groups, respectively. Comparable dose-independent enrichments of liver DHA were observed in mice fed CO and FO diets ( P < 0.001). Relative to the C group, lower fatty acid desaturase 1 ( Fads1 ) expression ( P < 0.005) was observed in the COH and FOH groups. Higher fatty acid desaturase 2 ( Fads2 ), peroxisome proliferator–activated receptor α ( Ppara ), and peroxisome proliferator–activated receptor γ ( Pparg ) ( P < 0.005) expressions were induced by CO. No impact of treatment on liver X receptor α ( Lxra ) or sterol regulatory element-binding protein 1c ( Srebp1c ) was evident. Conclusions: Oil from transgenic Camelina is a bioavailable source of EPA in mice. These data provide support for the future assessment of this oil in a human feeding trial.